2010
DOI: 10.1111/igc.0b013e3181e2abcc
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance Procedures for Patients Treated for Endometrial Cancer: A Review of the Literature

Abstract: No rationale (examination sensitivity/sensibility, cost-effectiveness, or patient's survival benefit) is available today for any particular follow-up protocol; follow-up procedures should probably be tailored according to different prognostic factors; only physical examination, including pelvic-rectal examination, showed some utility in detecting recurrence. In this uncertain setting, follow-up interval should be defined with the consideration of the patient's will.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 30 publications
1
41
0
Order By: Relevance
“…Recurrence of endometrial cancer is often symptomatic although reported to vary from 40-91% (23)(24)(25)27,28,(30)(31)(32). Most recurrences (70-95 %) occur within three years of initial treatment [31,33].…”
Section: Follow-up In Gynaecological Oncologymentioning
confidence: 99%
See 3 more Smart Citations
“…Recurrence of endometrial cancer is often symptomatic although reported to vary from 40-91% (23)(24)(25)27,28,(30)(31)(32). Most recurrences (70-95 %) occur within three years of initial treatment [31,33].…”
Section: Follow-up In Gynaecological Oncologymentioning
confidence: 99%
“…Recurrence of endometrial cancer is often symptomatic although reported to vary from 40-91% (23)(24)(25)27,28,(30)(31)(32). Most recurrences (70-95 %) occur within three years of initial treatment [31,33]. Symptomatic recurrences of endometrial cancer may have a worse prognosis than asymptomatic recurrences, as reported from recent studies carried out in Italy and Japan [34,35], although evidence is conflicting as other studies showed no such differences [23,36,37].…”
Section: Follow-up In Gynaecological Oncologymentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical practice, there appears to be no rationale available for any particular follow-up protocol 26. As there is a lack of any demonstrable survival benefit for the follow-up of gynaecological cancer patients, other schedules of care could be considered.…”
Section: Introductionmentioning
confidence: 99%